Rising U.S. Earnings Inequality and Family Labor Supply: The Covariance Structure of Intrafamily Earnings - Hyslop, Dean R (American Economic Review, 2001)
This paper studies the labor supply contributions to individual and family earnings inequality during the period of rising wage inequality in the early 1980's. Working couples have positively correlated labor market outcomes, which are almost entirely attributable to permanent factors. An intertemporal family labor supply model with this feature is used to estimate labor supply elasticities for husbands of 0.05, and wives of 0.40. This implies that labor supply explains little of the rising annual earnings inequality for married men, but over 20 percent of the rise in family inequality and 50 percent of the modest rise in female inequality. (JEL C23, J22)